Bispecific antibodies—effects of point mutations on CH3-CH3 interface stability. (5th December 2022) - Pomarici, Nancy D; Fernández-Quintero, Monica L; Quoika, Patrick K; Waibl, Franz; Bujotzek, Alexander; Georges, Guy; Liedl, Klaus R
Abstract: A new format of therapeutic proteins is bispecific antibodies, in which two different heavy chains heterodimerize to obtain two different binding sites. Therefore, it is crucial to understand and optimize the third constant domain (CH 3-CH 3) interface to favor heterodimerization over homodimerization, and to preserve the physicochemical properties, as thermal stability. Here, we use molecular dynamics simulations to investigate the dissociation process of 19 CH 3-CH 3 crystal structures that differ from each other in few point mutations. We describe the dissociation of the dimeric interface as a two-steps mechanism. As confirmed by a Markov state model, apart from the bound and the dissociated state, we observe an additional intermediate state, which corresponds to an encounter complex. The analysis of the interdomain contacts reveals key residues that stabilize the interface. We expect that our results will improve the understanding of the CH 3-CH 3 interface interactions and thus advance the developability and design of new antibodies formats. Graphical Abstract: